COVID-19 booster vaccination in rural community pharmacies. Issue 5 (27th January 2023) - Gamble, Abigail; Hastings, Tessa J.; Westrick, Salisa C.; Smith, Megan; Hannings, Ashley N.; Robinson, Jessica M.; Rosenthal, Meagen; Kiser, Stephanie N.; Curran, Geoffrey; Carpenter, Delesha M.
Abstract: This study assessed rural community pharmacists' attitudes about COVID-19 vaccine booster doses and explored whether rural pharmacies offered these booster doses. Of the 80 rural Southeastern U.S. pharmacists who completed the online survey, the majority (n = 68, 85 %) offered boosters and 42 (52.5 %) had received the booster themselves. Alabama and Mississippi offered boosters less often than other states, and pharmacists who had foregone receiving COVID-19 vaccination or booster doses were less likely to offer the booster to their patients. Additionally, many pharmacists reported that they and their patients felt the booster was not needed. Community pharmacies provide access points for the COVID-19 booster in rural areas. Interventions for both pharmacists and patients are needed to address hesitancy and improve booster uptake in these communities.